Engagement Exchanges and the Collective Pursuit of Visibility on TikTok in the Brazilian Context - Araujo, Willian; Karhawi, Issaaf (AoIR Selected Papers of Internet Research, 2026)
This study investigates engagement exchanges among Brazilian TikTok users, decentralized and collective practices aimed at producing data and metrics to help profiles qualify for the platform’s monetization program. Through the analysis of 123 TikTok videos, the study reveals a dynamic marked by diffuse collaboration and an ethic of reciprocity, where strategic engagement is promoted to boost visibility and meet monetization criteria. These practices involve the use of Generative Artificial Intelligence (GAI), employing static images, videos, and audio to guide interactions. Creators leverage the platform’s affordances through data-driven strategies to "play the game" of the algorithm. Findings suggest that engagement exchanges differ from traditional platform labor structures, as they prioritize collective monetization eligibility rather than professional content creation. This distinguishes engagement exchanges on TikTok from engagement pods on Instagram, which focus on brand partnerships and long-term influencer careers. In the Brazilian context, these practices are shaped by historical labor precarity, reinforcing platform-driven aspirations of economic mobility while simultaneously obscuring exploitative labor dynamics. The findings also reveal an ongoing tension between reciprocity-based collaboration and TikTok’s individualistic monetization model.